WORKSHOP AND OPEN DISCUSSION ON THE INDUSTRIAL REVOLUTION 4.0 AND THE FUTURE VIEW OF EDUCATION - Januardi Januardi; Diana Widhi Rachmawati; Nova Pratiwi; Neta Dian Lestari; Masnunah Masnunah; Erma Yulaini; Chandra Kurniawan; Hendri Gunawan; Susanti Feipi Salegri (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2022)
: This Community Service (PkM) aims to provide insight to teachers and students of SMA Negeri 4 Pagar Alam about the industrial revolution 4.0 and share views on the future of Indonesian education through open discussions. The industrial revolution 4.0 referred to in this whorkshop activity includes the development of the industrial revolution itself, opportunities and challenges as well as a paradigm shift in education thanks to the birth of the industrial revolution 4.0. The implementation of this community service uses several methods, namely presentations and open discussions. Participants in this PkM activity are teachers and students of SMA Negeri 4 Pagar Alam. Through the workshops, participants gained insight into the industrial revolution 4.0 and the digitalization of all aspects of life, including the world of education. Through open discussions, participants get the opportunity to share their views on the future of education and how to optimize potential to become productive individuals in the era of the industrial revolution 4.0